CHARACTER EDUCATION-BASED ECOTOURISM DEVELOPMENT IN KERUJUK ECOTOURISM VILLAGE NORTH LOMBOK - Azkar, Muh.; Noviani, Dwi; Muhammadi, Qasem (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to explain the efforts made by the Tourism Awareness Group (Pokdarwis) of Kerujuk Ecotourism Village in community-based character education. Efforts are based on the realization that building character that has concern for the preservation of the natural environment is very important through a systematic and synergistic educational process between school education and community education. The research method uses a qualitative approach, with a case study type. Data collection through observation, interviews and documentation of activities carried out by Pokdarwis and the community of Kerujuk Ecotourism Village. The results showed that the Pokdarwis of Kerujuk Ecotourism Village initiated and implemented things that lead to the formation of the character of a generation who cares about fellow humans and also the surrounding nature. Ecotourism development is carried out by involving various levels of society, government, religious leaders, community leaders, educational leaders, youth leaders, and school-age children. Activities that support character education are mutual cooperation, compensation for orphans and the elderly, and educational games.